Specifying the Indicators of a Breeding TapeCassette Sowing Device for Sowing Grain Crops by Ears - M. E. Chaplygin; M. M. Shaykhov; A. S. Chulkov; A. V. Podzorov (Сельскохозяйственные машины и технологии, 2022)
A high efficiency of sowing grain crops by ears was noted in breeding and primary seed production. It was found that a seeder with working bodies for sowing by ears helps to significantly (up to 8 times) reduce labor intensity as well as maintain the variety purity in comparison with the use of manual labor.Research purpose To develop a seeder working section with a tape-cassette sowing device for sowing grain crops by ears in breeding and seed nurseries, and to substantiate the sowing device parameters necessary for the design of a multi-section grain seeder.Materials and methods In the course of the experiments, the authors proposed a schematic diagram, a program and a method for testing a cassette seeder working section for sowing by ears.  A sample of the seed section was examined in the laboratory. The ways of ensuring the variety purity in conditions of grain natural shedding were studied. A technology of sowing ears in capsules was used.Results and discussion It was proposed to equip the seeder cassette sowing device with a device for pushing the capsule with the ear out of the cassette tape cell. A mock-up model of a spiked seed drill section was developed. The operation of the tape-cassette sowing device was checked.Conclusions The advisable parameters of the cassette tape cells specified are as follows: the inner diameter is 2.3-2.5 centimeters, the length is 14.0-16.5 centimeters, the distance between the axes is 3-4 centimeters. A formula for calculating the number of cells in a cassette tape was obtained depending on the number of tape turns in the cassette. The initial requirements and terms of reference were developed for the experimental sample of the grain drill section. The data were summarized to design a multi-section seeder for sowing with ears.